PENGARUH OLAHRAGA TERHADAP GEJALA KLINIS RINITIS VASOMOTOR - , ANISA HAQUL KHOIRIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Vasomotor rhinitis was one of the most frequent type of non allergic rhinitis. The occurrence of vasomotor rhinitis could increase the risk of nasal complications such as sinusitis, rinosinusitis, nasal polyp, nasal polyposis, etc. Exercise is an activity that could minimize the severity of vasomotor rhinitis symptoms for its role of stabilizing excessive parasymphatic impulses. Objective: The objective of this study was to acknowledge the effectiveness of exercise towards the improvement of vasomotor rhinitis symptoms, also providing non pharmacological treatment which was more efficient to minimize the symptoms and prevent complications. Methods: This was an experimental study using nonrandomized one group only pre test and post test design. Rhinitis symptoms and exercise questionnaires were used to determine which subjects were included and exercise pattern in each subject. Rhinitis symptoms utility index were used to measure the score of vasomotor rhinitis symptoms. The result data were analysed using Wilcoxon Paired T-test and linear regression. Results: The relation between exercise and the decrease in vasomotor rhinitis symptoms were significantly observed by the p-value = 0,000 with Î± = 0,05. No significance were found for frequency of exercise where p-value = 0,942, however, the duration and intensity showed some significance where p-values were 0,025 and 0,023 respectively. Conclusions: Exercise had an expected capability to reduce the symptoms of vasomotor rhinitis. The frequency of exercise did not affect the outcome of the symptom reduction, however, the duration and intensity did give an impact in the outcome.